2014
DOI: 10.1186/1743-0003-11-63
|View full text |Cite
|
Sign up to set email alerts
|

Foot force direction control during a pedaling task in individuals post-stroke

Abstract: BackgroundAppropriate magnitude and directional control of foot-forces is required for successful execution of locomotor tasks. Earlier evidence suggested, following stroke, there is a potential impairment in foot-force control capabilities both during stationary force generation and locomotion. The purpose of this study was to investigate the foot-pedal surface interaction force components, in non-neurologically-impaired and stroke-impaired individuals, in order to determine how fore/aft shear-directed foot/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In this current study, we sought to compare the role of the Ia afferent spinal loop under two conditions during a locomotor pedaling task: (1) postural loaded pedaling, and (2) non-postural loaded pedaling, in the non-impaired and in the post-stroke nervous system. Based on the findings of our earlier studies [ 33 , 34 ], we found that foot force directional control during non-postural loaded seated pedaling were well regulated in people post-stroke, but became impaired when postural loads were imposed on the pedaling task. This poor control was further exaggerated with greater postural loads.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this current study, we sought to compare the role of the Ia afferent spinal loop under two conditions during a locomotor pedaling task: (1) postural loaded pedaling, and (2) non-postural loaded pedaling, in the non-impaired and in the post-stroke nervous system. Based on the findings of our earlier studies [ 33 , 34 ], we found that foot force directional control during non-postural loaded seated pedaling were well regulated in people post-stroke, but became impaired when postural loads were imposed on the pedaling task. This poor control was further exaggerated with greater postural loads.…”
Section: Introductionmentioning
confidence: 73%
“…As reported previously [ 33 ], we were successful in matching F N generated during the non-seated postural loaded conditions with the targeted F N that was generated during the seated conditions by adjusting the tilt angle of the backboard (15.20±2.24(SD) in stroke versus 17.23±2.49 in non-impaired at 30% effort; 20.40±2.95 in stroke versus 26.69±4.13 in non-impaired at 50% effort). Since F S magnitude is partially dependent upon overall push effort and foot orientation relative to the pedal [ 34 ], similar F N values, generated when the foot was secured in a neutral ankle position, allowed us to make valid comparisons of effort under seated and non-seated conditions within and between each group. Furthermore, to control for the sensitivity of the reflex to muscle length, the lower limbs were secured in locked boots that minimize ankle movement during the pedaling task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To execute successful locomotion, leg muscles have to be coordinated so as to generate foot forces of appropriate magnitude and direction to propel the center of mass forward (Neptune et al, 2001). In individuals with chronic post-stroke hemiparesis, however, inappropriate direction of foot forces during locomotion has been reported (Bowden et al, 2006; Turns et al, 2007; Liang and Brown, 2013, 2014), specifically, reduced propulsive forces accompanied by exaggerated braking forces have been observed in paretic legs (Olney and Richards, 1996; Bowden et al, 2006; Turns et al, 2007). Furthermore, the impaired paretic foot force control capabilities during locomotion are exacerbated when the stroke-impaired nervous system is required to control for postures in addition to the locomotor task.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impaired paretic foot force control capabilities during locomotion are exacerbated when the stroke-impaired nervous system is required to control for postures in addition to the locomotor task. During non-postural loaded locomotion, foot force directional control was well regulated in individuals post-stroke, but excessive forward directed shear forces were generated during postural loaded locomotion, and further exaggerated with higher postural loads (Liang and Brown, 2013, 2014). It has also been observed that impaired H-reflex gain was associated with this defective interaction of postural and locomotor control in individuals post-stroke (Liang and Brown, 2015).…”
Section: Introductionmentioning
confidence: 99%